Towards people-centered integrated transport: A case study of Shanghai Hongqiao Comprehensive Transport Hub. (October 2016) - Li, Linna; Loo, Becky P.Y.
Abstract: Multimodal integration has become a significant issue in urban sustainable transport; however, there are some challenges in practice, especially in the developing countries. Based on passengers' travel experience, this paper establishes a conceptual framework of multimodal integration that considers nine categories of interchange performance indicators at three different levels of the "integration ladder". This framework is illustrated by a case study of Shanghai Hongqiao Comprehensive Transport Hub in China, to identify the main barriers of multimodal integration inside the hub from a people-centered perspective. On one hand, observational survey was conducted to record the indicators about interchange facilities provision; on the other hand, 603 questionnaires were collected to reflect the passengers' perception of interchange services. Both surveys show that the lowest level of information integration has been achieved in this hub, but the moderate level of facilities and services integration and the highest level of ticketing and fare integration are still limited. Further improvement is expected with respect to multimodal services and ticketing, such as time coordination, luggage delivery facilities, through ticketing and interchange discount. Moreover, for people with different personal and travel characteristics, their perceptions of multimodal integration have some differences, which suggest that the design, operation, and management of urban transport hubs should be people-centered in the future. Highlights: A framework of "integration ladder" is proposed to evaluate interchange in urban transport hubs. The framework is applied to a major transport hub in China and identity the main barriers to integrated transport. Moderate level of service integration and highest level of ticketing integration are limited in China. Passengers with different personal and travel characteristics have different perceptions of integrated transport.